Optimalisasi Program Safari Layanan Perpustakaan Bung Karno Bagi Generasi Alfa Di Kota Blitar Melalui Penerapan Kaizen - Widyastuti, Anna; Hikmah, Khoirul (Otonomi, 2024)
A library is a source of knowledge that contains elements of buildings, collections, human resources, and equipment. The library is charged with being able to implement the concept of emotional branding to create a nuance that can cultivate emotional closeness between the library and the librarian that make the librarians will get benefit from the services provided and they will be loyal librarians, so the rate of use of the library will increase. The library is claimed to have a large knowledgeable human resources and have the ability to manage the library as an undertaking that does not stand by itself. This qualitative research aims to design a strategy to optimize library human resources as information speakers on the ‘Safari Layanan of Bung Karno Library’ to Alpha Generation in the Blitar City. The research results show that in general, this activity has gone well and is acceptable, understood by older participants in the Alpha generation classification. However, as an attempt to optimize and deliver more outcomes, the conventional process business used is better with adopt the concept of Kaizen to applying continuous learning from the evaluation of one activity already implemented to be an improvement for the next activity. Keywords: kaizen, library management, alpha generation.